Myanmar: Promoting Reconciliation between the Rohingya Muslims and Buddhists of Rakhine State - Weber, Katja (Social justice, 2017)
One of the most pressing challenges Myanmar confronts is the mistreatment of the Rohingya in Rakhine state. Although Aung San Suu Kyi's National League for Democracy's landslide victory in November 2015 has given reason for cautious optimism, a multistage process of reconciliation between the Rohingya and Rakhine Buddhists is critically needed to build sustainable peace and promote justice. Tracing Buddhist/Muslim relations and drawing on scholarship examining reconciliation events, we propose a three-stage reconciliation process for Rakhine State and scrutinize steps to be taken to promote reconciliation.